Preventing and detecting public sector corruption: case study of Yemeni central organization for control and auditing (COCA) - Assakaf, Ebrahim Ahmed Ali (2019)
This study explains the reasons for widespread corruption in Yemen and investigates the role and functions of the Central Organization for Control and Auditing (COCA), a public audit institution, in preventing and detecting public sector corruption. This study adopts an in-depth qualitative case study approach using the triangulation of data sources. Data were obtained through documentary evidence, observational notes, and interviews with expert auditors in COCA, the Supreme National Authority for Combating Corruption (SNACC) and the Ministry of Finance (MOF). The data gathered was analysed using thematic analysis aided by ATLAS.ti qualitative data analysis software. The results reveals that corruption exists in Yemen due to weaknesses in the economic, public administrative, legal and accountability systems, political influence and social-cultural factors. Most importantly, the study finds that COCA has an active role in detecting corruption by means of conducting normal or specific purpose audits. However, participants perceived that COCA was not successful in preventing corruption because the mechanisms of prevention were not either put into place or activated. The findings also reveals that COCA conducted financial and compliance audits, but that COCA did not conduct either a performance or a forensic audit, which are equally important in preventing and detecting corruption in the public sector. The study also reveals the external and internal challenges and obstacles that limit the role and functions of COCA in preventing and detecting corruption. Interestingly, the findings are congruent with the fraud triangle theory, which explains why corruption in Yemen is rampant; and accountability theory, which explains the role and functions of COCA in preventing and detecting public sector corruption. Lastly, the study makes recommendations for policy changes to improve COCA and issues a call for further research to better understanding of the role and functions of a public sector audit in preventing and detecting corruption.